Efficacy of olanzapine combined with magnesium valproate sustained release tablets in the treatment of mental disorders caused by uremic encephalopathy - LUO Jun-hui; CHEN Yan-hong (Linchuang shenzangbing zazhi)
Objective To explore the efficacy of olanzapine combined with magnesium valproate sustained release tablets in the treatment of patients with mental disorders caused by uremic encephalopathy. Methods Ninety-three patients with mental disorders caused by uremia encephalopathy(mainly manifested as hallucinations, paranoia, mania, abnormal excitement, etc.), who were admitted to our hospital from March 2013 to June 2018, were selected and divided into three groups: combined group(33 cases), single-use group(30 cases) and control group(30 cases). Patients in the combined group were treated with olanzapine combined with magnesium valproate sustained release tablets plus blood purification(hemodialysis twice + hemodiafiltration once per week) and symptomatic supportive treatment. Patients in the single-use group were treated with olanzapine plus blood purification(hemodialysis once + hemodiafiltration once per week) and symptomatic supportive treatment. Patients in the control group only received blood purification(hemodialysis twice + hemodiafiltration once per week) and symptomatic support treatment. The course of treatment is 2 weeks for all the groups. The clinical efficacy of the patients was assessed by the negative and positive scale(PANSS), and adverse reactions were observed in both the groups. Adverse reactions were assessed by the treatment emergent symptom scale(TESS). Results The PANSS scores in the combined group were significantly lower than those in the single-use group and the control group at weekends 1 and 2 of the treatment course, with difference of statistically significance(P<0.05). And the PANSS scores in the single-use group was significantly lower than in the control group at weekend 2, with difference of statistical significance(P<0.05). The patients in the combined group had better control of mental symptoms and the curative effect was more significant. There was no significant difference in TESS score between the two groups(P>0.05). Conclusions Olanzapine combined with magnesium valproate sustained release tablets for the treatment of uremic encephalopathy patients with mental disorders has more rapid response, higher control rate, and good and safe efficacy, and so can quickly control the patient’s mental symptoms. For uremic encephalopathy patients with mental disorders it can be promoted clinically.